The diversity of amphibian species in urban lake as ecological indicator for healthy aquatic environment - Hj. Baharuddin, Zainul Mukrim; Ramli, Lukman; Othman, Rashidi (Universiti Putra Malaysia, 2015)
Urban expanse problem causes degradation of biodiversity, while forest contemporaneous is experiencing defaunation alteration for the need of more living spaces. Consequently, the world has just been alerted with the inclination of the urban biodiversity. Human tendency to ignore healthy ecology causes the research on urban wildlife to be bawl in these recent years, which later lead to severe effects such as loss of natural habitat, fragmentation and disturbance. However, the research conducted specifically on amphibian as bioindicator to environmental changes is still very low, as it covers only 4 percent every decade analysis, though many researchers believe amphibian such as frog is the best indicator to healthy environment. Momentarily, this research aimed to identify and record the number of amphibian population that can be used as new bio-indicator for a healthy environment in Perdana Botanical Lake Garden, Kuala Lumpur. Four areas of wetlands were assessed and conducted on amphibian active time which is at night as well as landscape setting. Results showed that six amphibian species of Duttaphrynus melanostictus (Common Sunda Toad), Hylarana erythraea (Green Paddy Frog), Polypedates leucomystax (Four-line Tree Frog), Fejervarya cancrivora (Crab-eating Frog), Microphyla heymonsi (Dark sided chorus frof) and Fejervarya limnocharis (Indian Rice Frog) were observed. The highest species of amphibian recorded were Hylarana erythraea with (n=80) which were found at all stations of Wetland 2 (largest wetland) and two stations at Wetland 3 (natural wetland), while others were less than (n=10).